Experimental study on baling rice straw silage - Wang, Defu; Buckmaster, Dennis R; Jiang, Yiyuan; Hua, Jinling (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: For resolving harvesting technology of fresh rice straw silage and plugging of the round steel-roll baler in China, experimental researches were carried out. For harvesting technology, baling silage and chopping silage were experimented. For the round baler, three kinds of feeding rolls equipped for enhancing feeding capability were experimented separately by reliability. Experimental results indicate: harvesting technology of baling fresh rice straw as silage is practicable; slicing-disc feeding rolls can be used to the baler to resolve plugging in straw-baling course. And through further experiments by reliability and density, optimal structure of the feeding roll is obtained: big and small slicing-discs arranged in interval and inclination, distance between slicing-discs being 30–40 mm. Keywords: silage harvesting, rice straw, round baler, feeding mechanism DOI: 10.3965/j.issn.1934-6344.2011.01.020-025 Citation: Wang Defu, Dennis R.Buckmaster, Jiang Yiyuan, Hua Jinling. Experimental study on baling rice straw silage. Int J Agric & Biol Eng, 2011; 4(1): 20<span style="font-size: 9pt; color: black; font-family: